Business model innovation under strategic transformation. Issue 5 (4th May 2022) - Holtström, Johan
ABSTRACT: Strategic transformation is a driver for business model innovation. This study identifies key aspects and activities of business model innovation in a high-tech industry utilising strategic transformation. The study takes its departure in an aircraft engine manufacturer dominated by military products that evolves into a high-tech developing company competing on an open market. Findings support previous research on changes in the defence industry such as risk sharing, a need to identify core technologies, and the importance of efficiency related to profitability. The study contributes to a greater understanding of how business models develop under strategic transformation, and an understanding of the need for change and what capabilities are required to leave previous strategic development behind and undertake a new path to future development.